2013
DOI: 10.1088/1475-7516/2013/08/006
|View full text |Cite
|
Sign up to set email alerts
|

Influence of reheating on the trispectrum and its scale dependence

Abstract: We study the evolution of the non-linear curvature perturbation during perturbative reheating, and hence how observables evolve to their final values which we may compare against observations. Our study includes the evolution of the two trispectrum parameters, gNL and τNL, as well as the scale dependence of both fNL and τNL. In general the evolution is significant and must be taken into account, which means that models of multifield inflation cannot be compared to observations without specifying how the subseq… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 88 publications
(165 reference statements)
2
25
0
Order By: Relevance
“…It should be noted that predictions for non-linearity parameters can change by factors of order one during (p)reheating if an adiabatic regime has not been reached previously [439,440]; that non-gaussianities are subject to change and often transient as long as the adiabatic regime is not reached was pointed out in [428,441] see also [442] for subsequent work. A turn in field space may arise due to the ekpyrotic potential: as the fields need to follow the ridge of the potential in order to yield a scale-invariant spectrum, see Sec.…”
Section: E Non-gaussianitiesmentioning
confidence: 97%
“…It should be noted that predictions for non-linearity parameters can change by factors of order one during (p)reheating if an adiabatic regime has not been reached previously [439,440]; that non-gaussianities are subject to change and often transient as long as the adiabatic regime is not reached was pointed out in [428,441] see also [442] for subsequent work. A turn in field space may arise due to the ekpyrotic potential: as the fields need to follow the ridge of the potential in order to yield a scale-invariant spectrum, see Sec.…”
Section: E Non-gaussianitiesmentioning
confidence: 97%
“…For two-field inflation, numerical studies [29,37,38] have demonstrated that observables such as the power spectrum P(k), and the local shape bispectrum parameter f NL can be very sensitive to the details of reheating. This sensitivity was quantified in Ref.…”
Section: Introductionmentioning
confidence: 99%
“…In the context of multifield theories the analysis becomes complicated and most work has been restricted to separable potentials [16,17,18,19,20,21,22], but interacting fields have been considered for flat target spaces in refs. [23,24,25], and a discussion admitting curved inflaton targets can be found in ref. [26,27].…”
Section: Introductionmentioning
confidence: 99%